Positive Recurrence and Extinction of Hybrid Stochastic SIRS Model with Nonlinear Incidence Rate - Liang Chen; Shan Wang (Journal of Mathematics)
In this paper, the dynamic behavior of a class of hybrid SIRS model with nonlinear incidence is studied. Firstly, we provide the condition under which the positive recurrence exists and then give the threshold R0S for disease extinction, that is, when R0S<1, the disease will die out. Finally, some examples are constructed to verify the conclusion.